2020
DOI: 10.1021/acsanm.0c00244
|View full text |Cite
|
Sign up to set email alerts
|

Differing Affinities of Gold Nanostars and Nanospheres toward HeLa and HepG2 Cells: Implications for Cancer Therapy

Abstract: Gold nanoparticles have potential applications for the diagnosis and treatment of diseases due to their optical, sensing, and biological properties. Gold nanoparticles can be used as nanocarriers for the delivery of therapeutic agents or as nanoprobes to detect and monitor intracellular events. Studying their localization and properties in cells is an essential step toward developing nanoparticle products for in vivo use. Raman spectroscopy is a powerful and noninvasive method that we used to investigate how t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…We applied the same strategy to quantify the uptake of particles in different regions of cells. Considering the size range of each type of particle (measured by DLS), we used ImageJ to count the average number of three different types of NPs in two different cell lines 12 . Student’s t -test was used to compare statistical data, and differences were considered significant at p < 0.05.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We applied the same strategy to quantify the uptake of particles in different regions of cells. Considering the size range of each type of particle (measured by DLS), we used ImageJ to count the average number of three different types of NPs in two different cell lines 12 . Student’s t -test was used to compare statistical data, and differences were considered significant at p < 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…Raman spectroscopy (RS) and infrared absorption (IR) have also been used to detect and localize NPs at the subcellular level 12 . The low spatial resolution of the IR technique has limited the application of this technique for intracellular diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Different affinities to different subcellular elements may also be an influential factor in the level of impact on mechanobiological properties. Our previous study observed that gold NPs have different affinities to cytoskeletal components. , This morphology-dependent behavior of NPs may influence NBI and, subsequently, their impacts on cellular elasticity. However, a further detailed study is required to investigate the role of NP morphology in their interaction with intracellular proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Zetasizer Nano ZS90 (Malvern Instruments, UK) was utilized to characterize the size of gold NPs. The Brookhaven Zeta Plus electrophoresis instrument was used to characterize the zeta potential of particles under ambient temperature as described previously …”
Section: Methodsmentioning
confidence: 99%
“…They also observed that MT networks are damaged and shrunken upon interaction with gold NPs compared to control cells. NPs might have different affinities to different subcellular structures depending on their physicochemical properties [152,153]. Wen et al [154] found that silver NPs tend to bind actin rather than tubules under electrostatic interactions.…”
Section: Impacts Of Nanoparticles On Structural Elements and Morphology Of Cellsmentioning
confidence: 99%